Social Learning Strategies of Indonesian University Learners of English as L2: A Mixed-Method Study - Rajagukguk, Erison Saoloan; Subekti, Adaninggar Septi (Loquen, 2023)
The present study was conducted to find the extent of the use of social learning strategies (SLS) by Indonesian learners of English as a second/foreign language (L2) from non-English departments. This study employed a sequential explanatory mixed-method design. 125 learners participated in the survey and six participants in the interviews. From descriptive statistics, the study found that generally, learners' use of SLS was at a high level. The majority reported they practised English with their peers, asked their teachers for help and corrections, and ask people to slow their speech down or repeat it if they did not get what was said. From the Thematic Analysis of the interview data, the study found that watching videos and quizzes in L2 classes encouraged learners to ask questions and do relevant discussions with peers. Also, learners mostly asked their peers questions when facing difficulties in L2 vocabulary and pronunciation. Implications included designing activities promoting psychologically safe environments in L2 classes where learners can use their SLS more optimally. Limitations are acknowledged and possible relevant future studies are suggested.